The effect of service quality, marketing strategy and distribution efficiency on sales with the mediation of consumer trust - Suhera, Rizki Dila; Suhardi, Suhardi (Economic: Journal Economic and Business, 2026)
This study analyzes the influence of service quality, marketing strategy, and distribution efficiency on sales performance with consumer trust as a mediating variable in the beef sales business of MSMEs in Toboali Market. The study used a quantitative approach involving 160 respondents and was analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results showed that service quality and distribution efficiency had a positive and significant effect on sales performance, both directly and through consumer trust. Conversely, marketing strategy did not have a significant effect on consumer trust or sales performance. These findings indicate that in the context of traditional markets and fresh food products, consumers prioritize service quality, product consistency, and smooth distribution over conventional marketing activities. This study confirms the role of consumer trust as an important mediator linking operational practices with sales performance and provides managerial implications for the development of fresh food MSMEs.